Disruption of a novel member of a sodium/hydrogen exchanger family and DOCK3 is associated with an attention deficit hyperactivity disorder-like phenotype. Issue 10 (20th October 2003) - de Silva, M G; Elliott, K; Dahl, H-H; Fitzpatrick, E; Wilcox, S; Delatycki, M; Williamson, R; Efron, D; Lynch, M; Forrest, S
Abstract : Background: Attention deficit hyperactivity disorder (ADHD) is a complex condition with high heritability. However, both biochemical investigations and association and linkage studies have failed to define fully the underlying genetic factors associated with ADHD. We have identified a family co-segregating an early onset behavioural/developmental condition, with features of ADHD and intellectual disability, with a pericentric inversion of chromosome 3, 46N inv(3)(p14:q21). Methods: We hypothesised that the inversion breakpoints affect a gene or genes that cause the observed phenotype. Large genomic clones (P1 derived/yeast/bacterial artificial chromosomes) were assembled into contigs across the two inversion breakpoints using molecular and bioinformatic technologies. Restriction fragments crossing the junctions were identified by Southern analysis and these fragments were amplified using inverse PCR. Results: The amplification products were subsequently sequenced to reveal that the breakpoints lay within an intron of the dedicator of cytokinesis 3 ( DOCK3 ) gene at the p arm breakpoint, and an intron of a novel member of the solute carrier family 9 (sodium/hydrogen exchanger) isoform 9 ( SLC9A9 ) at the q arm. Both genes are expressed in the brain, but neither of the genes has previously been implicated in developmental or behavioural disorders. Conclusion: These two disrupted genes are candidates for involvement in the pathway leading to the neuropsychological condition in this family.